Urban planning for physically disabled people’s needs with case studies - Shahraki, Abdol Aziz (Spatial information research (Online), 2021)
The aim of this study is to provide urban planning procedures tailored to the needs of disabled people. For this, it analyzes the problems of disabled people, especially physically disabled people, for living in Iran’s cities. It also analyses various planning and design characteristics of buildings in Iranian cities. Research methods of this paper are problem-oriented theoretical studies, case studies, a weighted sum method, and a Benchmarking technique. The methods assist to provide relevant standard indicators and a theoretical framework for the comparison of the cities to an optimal alternative. A case study strategy to gather data for certain comparisons and present a disabled-oriented model of urban planning has been performed. The weighted sum method dedicates quantitative scores and performs the comparison and judgment. Finally, this paper concludes that the cities in Iran are not appropriate to the physical and administrative needs of the disabled. This study finds that buildings in Iranian cities often lack the necessary standards for the needs of the disabled. The outcomes of this research concerning urban planning for disabled people will assist better disabled-oriented urban planning, design, and development everywhere in the world.